Actions of estrogens on glial cells: Implications for neuroprotection - Arevalo, María-Angeles; Santos-Galindo, María; Bellini, María-José; Azcoitia, Iñigo; Garcia-Segura, Luis M. (Biochimica et biophysica acta, 2010)
Glial cells are directly or indirectly affected by estradiol and by different estrogenic compounds, such as selective estrogen receptor modulators. Acting on oligodendrocytes, astrocytes and microglia, estrogens regulate remyelination, edema formation, extracellular glutamate levels and the inflammatory response after brain injury. In addition, estradiol induces the expression and release of growth factors by glial cells that promote neuronal survival. Therefore, glial cells are important players in the neuroprotective and reparative mechanisms of estrogenic compounds.